An investigation of the influence of the morphological indexes of trees on the outdoor microclimate at high altitude in summer - Zhang, Yingzi; Chen, Lixing; Sun, Chen; Fu, Yunchao; Xie, Yibing (Frontiers in Environmental Science, 2023)
Trees have significant effects of shading, humidifying, and cooling, and at the same time, they can create a more comfortable space for people. However, due to the complexity of their own biology, there are also some differences in the regulation mechanism of the space microclimate among different trees. Under the background of a high altitude and cold climate, based on field measurements and numerical simulation, this paper discussed the effects of the morphological indexes, including the height, crown width, leaf area index (LAI), and under branch height of trees and their interactions on the urban microclimate and thermal comfort in Lhasa city. The study revealed the following: (1) LAI is the key factor affecting the thermal environment and thermal comfort of the space under a tree, followed by height and crown width, and the improvement potential of under branch height is relatively weak. (2) The interaction between height and LAI and crown width affects the thermal comfort of the space under a tree. (3) In summer, the optimal combination of tree morphological indexes in Lhasa is LAI = 2 m2/m3, height = 12 m, crown width = 11 m, ground reflectance = 0.2.